2017
DOI: 10.1097/bcr.0000000000000528
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Randomized Controlled Trial to Assess an e-Learning on Acute Burns Management

Abstract: An e-learning tutorial was developed to cover the basic aspects of acute burns management. The aim of this study was to provide objective educational evidence supporting the role of an e-learning on acute burns management ("basic burns management" or BBM) when compared with traditional teaching methods when introduced in different medical school settings around the world. A multicenter randomized controlled trial was conducted at the University of Pittsburgh, Peninsula College of Medicine and Dentistry, and St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…The target groups included medical students (n = 30) [ 24 35 , 37 , 38 , 40 , 41 , 48 , 49 , 56 59 , 61 , 62 , 64 66 , 69 71 ], nursing students (n = 16) [ 36 , 42 , 43 , 45 , 47 , 50 , 52 55 , 60 , 63 , 67 , 68 , 72 ], midwifery students (n = 1) [ 51 ], and dental students (n = 3) [ 39 , 44 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The target groups included medical students (n = 30) [ 24 35 , 37 , 38 , 40 , 41 , 48 , 49 , 56 59 , 61 , 62 , 64 66 , 69 71 ], nursing students (n = 16) [ 36 , 42 , 43 , 45 , 47 , 50 , 52 55 , 60 , 63 , 67 , 68 , 72 ], midwifery students (n = 1) [ 51 ], and dental students (n = 3) [ 39 , 44 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study reported that a shareable weblink was used but offered no specific information [ 32 ]. Regarding the remaining four studies, four different virtual learning environments were used: Basic Burns Management e-learning tool [ 66 ], Education in Dermatology [ 41 ], the VBLaST-PC system for fundamentals of laparoscopic surgery [ 70 ], and the CASUS—a case-based multimedia learning and authoring system for undergraduate, postgraduate and continuing education [ 28 ]. Thus, the studies showed substantial variation in the learning environment, making it difficult to draw conclusions of any kind.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a tremendous effort to develop teaching methods and tools making use of ever-increasing technological advancement. A review of medical literature over the last fifteen years demonstrates a wide variety of tools developed and studied, from 'home-grown' e-learning modules [14][15][16][17][18] to proprietary internet accessible computer aided learning systems [19][20][21][22][23][24]. These materials include both medical knowledge and clinical decision-making concepts that often take the form of case studies, many of which are interactive.…”
Section: The New Face Of Medical Educationmentioning
confidence: 99%
“…There is clear evidence to support that electronic learning modalities can offer equivalent or even superior results than 'traditional' methods, and that students appear to find many of these experiences satisfactory, sometimes rating them more favorably than textbook learning or lecture experiences [14,15,18,19,24,25]. All these different options must be considered within the learning objectives set by the medical schools.…”
Section: The New Face Of Medical Educationmentioning
confidence: 99%